KONSEP KEADILAN MENURUT HUKUM MURNI HANS KELSEN DALAM RELEVANSINYA DENGAN PENEGAKAN HUKUM DI INDONESIA - , R. Arry Mth,. Soekowathy, Drs,SH,M.Hum., Prof. Dr. H. R. Soejadi, S.H. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
This philosophy reasearch entitles âThe Concept of Justice According to Hans Kelsenâs Pure Law Enforcementâ. Its is a review on law philosophy aiming at addressing the questions of philosophy comprehensively and exhaustively abaut whether justice, as Hans Kelsenâs thought in pure law elaborates the aspects of pure law prevailed in society related to de definition of law and the concept of justice viewed from the aspect of its law philosophy. The concept of justice prevalied in Pure Law recently is not suitable with the society and justice wich the reality of lau has hurt thought and peopleâs heart. Besides looking for the relevance by determining the way as well as finishing the law problems due to the deviation of the law practices in the society caused by law deterioration or other ways opposed to moral values and law values which are considered deviating from the real ideas of law because law has been interfered by political with the elements of psychology, sociology, ethics, and the relevant theories so that the purity of law becomes ignored and negated. It then makes the essence of law blurred and eliminates the limits determined by the existing law regulations. The research done library research because the formal object and the materials were obtained from literature, the result of searching, and the comparative study of the law experts related to primary source discussing, and the matters of Law Philosophy and the sense of justice in Hans Kelsenâs Positive Law. Those sources were supported by various literatures of justice and jurisprudence that had been the standarts in the process of trial that had been proven in the implementation of trial practices. After that, the concept of Law Philosophy was explained as conceptual framework philosophically about three basic components, those were sense of justice, law, and positive law prevailed and they had been applied so they had correlations and gave aspiration in the law philosophy-based writing so the results were findings initiated by law practitioners in the fields as well as the life practices in society, nations, and state. The result obtains are the findings of Hans Kelsenâs thinking pattern explanning about the concept of the justice. Besides, the others result are finding out the purity of law and explaining how the real purposes of the law are. This research actually tried to answer the definition of justice in das sein and in das sollen rather than the law itself because the pure theory of law is jurisprudence not political law and is named as âpureâ law because it explains law and tries to clean the object of discussions from everything which is not related to the law. The review of this concept is to clean law science from forgein elements as Hans Kelsenâs thinking basis.